Thiophosphate-Based Covalent Organic Framework (COF) or Porous Organic Polymer (POP)? - Christophe Menendez; Yannick Coppel; Baptiste Martin; Anne-Marie Caminade (Macromol)
There are few examples of covalent organic frameworks (COFs) based on phosphorus as the building element, probably because the structure of most phosphorus derivatives is pyramidal, which may prevent the stacking expected for classical 2-dimensional COFs. In addition, they are generally associated with linear difunctional derivatives. In this paper is reported the original association of a trifunctional 3-D compound with a trifunctional 2-D compound in an attempt to get a new COF. The condensation reaction between a thiophosphate derivative bearing three aldehydes and the trihydrazinotriazine has been carried out with the aim of obtaining either a COF or simply a porous organic polymer (POP), consisting in both cases of associated macrocycles, affording a new covalent triazine framework (CTF). The material resulting from this condensation has been characterized by multinuclear MAS NMR (31P, 1H, and 13C), IR, and thermogravimetric analysis (TGA). All these data confirmed the condensation reactions. However, BET (Brunauer–Emmett–Teller) measurements indicated that the porosity of this material is low. Trapping dyes in solution, as a model of pollutants, by the insoluble porous material 3 has been attempted.